Serum potassium abnormalities in chronic kidney disease: prevalence, patient characteristics and clinical outcomes. Issue 11 (24th October 2021) - Brookes, Elizabeth M.; Snider, Jonathan; Hart, Graeme K.; Robbins, Raymond; Power, David A.
Abstract: Background: Abnormalities in serum potassium are a well known complication of chronic kidney disease (CKD), but little is known about their impact on inpatient outcomes. Aims: To better understand the role of dyskalaemia in hospital in‐patients, we assessed the epidemiology of potassium disorders among CKD patients, and the association between admission potassium and inpatient mortality or intensive care unit (ICU) requirement. Methods: This retrospective hospital‐based cohort study ( n = 11 156) included patients with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 admitted to Austin Health between 2014 and 2018 and who had an admission potassium value. Dialysis patients or those with a renal transplant were excluded. Multivariate logistic analysis was conducted to identify factors associated with hyperkalaemia (≥5.5 mmol/L) and hypokalaemia (<3.5 mmol/L). Odds ratios for inpatient mortality and ICU admission between potassium categories were obtained by multivariate regression with adjustments for demographics, renal function and comorbidities. Results: Hyperkalaemia and hypokalaemia were present in 6.86% and 2.94% of hospital admissions respectively. In multivariate regression male sex, lower eGFR, diabetes and cardiac failure were associated with higher odds of hyperkalaemia. Thiazide diuretics, loop diuretics, infectious disease and endocrine pathology were associated with higher odds of hypokalaemia. A U‐shaped association was noted between potassium and inpatient mortality. Potassium <4.0 mmol/L and ≥5.0 mmol/L was associated with increased mortality. Only patients with potassium ≥5.5 mmol/L had increased ICU admission risk. Conclusion: Derangements in potassium frequently occur in CKD inpatients and are independently associated with higher mortality and ICU requirement. Further studies are required to determine whether interventions to maintain normokalaemia improve outcomes in this population.